KUALITAS PELAYANAN IZIN GANGGUAN PADA BADAN PELAYANAN PERIZINAN TERPADU KOTA PALU - Muzani, Muzani (Katalogis, 2015)
This research aims at finding out how the quality of interference license service at Integrated Licensing Service Agency, Palu. The types of data used are primary data and secondary data. The techniques of the data collection were observations, interviews, documentations, and triangulation. The informants were taken by using purposive sampling technique. The data analysis used in this research is a model of Miles and Huberman, namely data reduction, data presentation, and conclusion. The theory used is the theory of Zethmal, Parasuraman and Berry, which consists of 5 (five) dimensions: tangibles, reliability, responsiveness, and empathy assurance. Based on the results of the research, it is concluded that the quality of Interference License Service / HO on Integrated Licensing Service Agency Palu, is not maximum. First; tangibles dimension, the infrastructure is inadequate as lacking the breadth of the lounge and the available seats are not in accordance with the number of applicants, as well as the number of public toilets which are inadequate. But in terms of the officers’ appearance and neatness, it is categorized as good. Second; reliability dimension, the ability of the officers in using tools is very good, but the service provided do not fully refer to the operational procedure standard. Third; responsiveness dimension, the response of the officers in receiving applicants’ complaint has been very good, but the speed in completing the issuance of licenses is not maximal. Fourth; assurance dimension, the guarantee given by the officers to the applicants has not been on time. But the license fee has been imposed in accordance with applicable regulations. Fifth; empathy dimension, the service provided is not discriminatory and service providing is always polite and friendly. Thus, of the five dimensions of service quality above, there are still some sub dimensions that need to be fixed, so that the quality of the services provided can be maximized.